Effects of estrogen and/or progesterone on the changes occuring in the uterine luminal epithelium of ovariectomized rats - Oner, H; Oner, J; Kukner, A; Ozan, E (Veterinary Faculty, Univ Beogradu, 2002)
This study examined the histological changes that occurred in the uterine luminal epithelium after ovariectomy and subsequent administration of ovarian hormones, Female Wistar-albino rats that were 6 weeks of age were used. The rats were subject to bilateral ovariectomy and then estrogen and progesterone (2,5 mg/kg) were given alone or together. Effects of ovarian hormones on the uterine luminal epithelium were examined under the light microscope. In the ovariectomized and progesterone injected animals, the uterine epithelium atrophied and the luminal epithelial cell height decreased. In the estrogen injected animals the uterine tissue was more hyperemic and filled with more luminal fluid than in the other groups. Estrogen treatment induced a significant increase in the epithelial cell height and a marked thickening in the basement membrane of epithelial cells. No histologically identifiable changes were observed in the uterine luminal epithelial cells after estrogen + progesterone treatment, except for well-developed endometrial glands. This study suggests that the uterine luminal epithelial cell height increases with estrogen treatment, while the uterine tissue atrophies after ovariectomy and progesterone treatment.
Keywords: estrogen; microscopy; ovariectomy; progesterone